(untitled) (Eurasian Medical Research Periodical, 2022)
The main focus of this study was to assess awareness creation through information and communication technology and exclusive breastfeeding practices among nursing mothers in Akwa Ibom north-west senatorial district. Ex-post facto design was adopted was for this work. The area covered by the researcher was Akwa Ibom North-West Senatorial District. The target population for this study was 200 registered nursing mothers in the healthcare facilities. A purposive sampling technique was used to select 200 nursing mothers who constituted the sample size used for the study. The instrument used in this study for data collection was a questionnaire titled " Awareness Creation through Information and Communication Technology and Exclusive Breastfeeding Practices among Nursing Mothers Questionnaire” (ACICTEBPNMQ). In order to establish both the face and content validity of the research instruments, the drafted instrument was given to three research experts in the Department of Physical and Health Education, Faculty of Education, University of Uyo. Apart from the research questions answered with descriptive statistics, independent t-test statistics was used to test the hypotheses and the test for significance was at the probability alpha level of 0.05. The study concluded that every nursing mother is at liberty to access exclusive breastfeeding information regardless of geographical dwelling location and that the Christian nursing mothers access the exclusive breastfeeding information more than traditionalists. It also proved that married women have access to exclusive breastfeeding information more than the single nursing mothers. Finally, the result proved that the highly educated nursing mothers have access to exclusive breastfeeding information more than the lowly educated nursing mothers. One of the recommendations made in the study was that the use of ICT in disseminating the practice of exclusive breastfeeding has, to a large extent, brought an end to religious sentiment and so effort should be doubled to bring it to the peak or very large extent.